Properties and uses of propolis in dentistry: a review - López González, Lorena (2022)
L Propolis is a product derived from bees and consists of a dark-colored sticky material obtained from different plants and mixed with wax, which is used to protect beehives. It has therapeutic qualities, so the objective of this study was to carry out a bibliographic review of the properties and uses of propolis in dentistry.Methodology: A literature search was carried out on the applications of propolis in dentistry in the databases PubMed, Imbiomed, Medigraphic, SciELO and Google Scholar in the period from March 2010 to March 2020, using the keywords: propolis, characteristics, properties and uses of propolis.Results. Thirty-nine articles reporting results in relation to its properties and uses in dentistry were included. The main properties: antimicrobial, anti-inflammatory, immunomodulatory and healing, basically attributed to the bioactive compound Flavonoids. Propolis is used in dentistry for different treatments: prevention of dental caries, endodontics, periodontics, prosthodontics and oral surgery.Currently, special attention has been paid to the applications of propolis, being a natural product useful for treatments in different areas of dentistry where its great efficacy has been demonstrated.